TRANSPLANTASI KEPASTIAN DAN PERLINDUNGAN HUKUM DALAM SISTEM PENDAFTARAN HAK ATAS TANAH YANG BERKEADILAN - Suharyono, Suharyono (Universitas Islam Negeri Raden Fatah Palembang, 2016)
Legally, the main purpose of land registration is to create legal certainty and ensure the protection of the law. But at the level of its implementation, the legal certainty of land registration is yet to be felt by the community. This means that in fact along our lives are still considered to be no legal certainty of the existence of land registration in this country, because the certificate has not fully guarantee the land rights of a person. This fact needs to be overcome by transplanting certainty and legal protection in the system of registration of land rights with justice. It can be done through: transplant certification bureaucracy in the system of registration of land rights and transplantation of responsibility system of BPN/ Land Office officials. ملخص: من الناحية القانونية، والغرض الرئيسي من تسجيل الأراضي هو خلق اليقين القانوني وضمان حماية القانون. ولكن على مستوى تنفيذها، وبعد أن شعر اليقين القانوني لتسجيل الأراضي من قبل المجتمع. وهذا يعني أنه في واقع الأمر على حياتنا لا تزال تعتبر أنه لا يوجد يقين قانوني من وجود تسجيل الأراضي في هذا البلد، لأن الشهادة قد لا يضمن بالكامل حقوق ملكية الأراضي للشخص. يحتاج هذه الحقيقة التي يجب التغلب عليها عن طريق زرع اليقين والحماية القانونية في نظام تسجيل حقوق ملكية الأراضي مع العدالة. يمكن أن يتم ذلك من خلال: زرع شهادة البيروقراطية في نظام تسجيل حقوق ملكية الأراضي وزرع نظام المسؤولية للمسؤولين BPN / دائرة الأراضي.